Consumption of Buglossoides arvensis seed oil is safe and increases tissue long-chain n-3 fatty acid content more than flax seed oil – results of a phase I randomised clinical trial. (8th January 2016) - Lefort, Natalie; LeBlanc, Rémi; Giroux, Marie-Andrée; Surette, Marc E.
Abstract: Enrichment of tissues with ≥20-carbon n -3 PUFA like EPA is associated with positive cardiovascular outcomes. Stearidonic acid (SDA; 18 : 4 n -3) and α-linolenic acid (ALA; 18 : 3 n -3) are plant-derived dietary n -3 PUFA; however, direct comparisons of their impact on tissue n -3 PUFA content are lacking. Ahiflower ® oil extracted from Buglossoides arvensis seeds is the richest known non-genetically modified source of dietary SDA. To investigate the safety and efficacy of dietary Ahiflower oil, a parallel-group, randomised, double-blind, comparator-controlled phase I clinical trial was performed. Diets of healthy subjects ( n 40) were supplemented for 28 d with 9·1 g/d of Ahiflower (46 % ALA, 20 % SDA) or flax seed oil (59 % ALA). Blood and urine chemistries, blood lipid profiles, hepatic and renal function tests and haematology were measured as safety parameters. The fatty acid composition of fasting plasma, erythrocytes, polymorphonuclear cells and mononuclear cells were measured at baseline and after 14 and 28 d of supplementation. No clinically significant changes in safety parameters were measured in either group. Tissue ALA and EPA content increased in both groups compared with baseline, but EPA accrual in plasma and in all cell types was greater in the Ahiflower group (time × treatment interactions, P ≤ 0·01). Plasma and mononuclear cell eicosatetraenoic acid (20 : 4 n -3) and docosapentaenoic acid (22 : 5 n -3) content also increased significantly in the Ahiflower group compared with the flax group. In conclusion, the consumption of Ahiflower oil is safe and is more effective for the enrichment of tissues with 20- and 22-carbon n -3 PUFA than flax seed oil.